2015
DOI: 10.2169/internalmedicine.54.3742
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Thyroid Enlargement Following Metastasis of Lung Adenocarcinoma

Abstract: A 55-year-old man presented with a rapidly enlarging thyroid. He had been diagnosed with lung adenocarcinoma nine months earlier. Computed tomography (CT) and ultrasound (US) detected reticular cord-like structures, but no nodules, in the thyroid. A fine-needle aspiration biopsy (FNAB) of the thyroid revealed thyroglobulin-negative adenocarcinoma cells, thus establishing the diagnosis of diffuse thyroid metastases of lung cancer. Moreover, the fluid demonstrated milky chyliform effusion. This case suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Thus, the ultrasonographic findings obtained in this case are definitely valuable. Our report has revealed that the characteristic ultrasonographic features seen in our patient are analogous to those observed in diffuse thyroid metastases from other primary cancers [2, 14], and that color Doppler ultrasonography may be quite useful for the correct diagnosis of diffuse thyroid infiltration of gastric and other cancers.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…Thus, the ultrasonographic findings obtained in this case are definitely valuable. Our report has revealed that the characteristic ultrasonographic features seen in our patient are analogous to those observed in diffuse thyroid metastases from other primary cancers [2, 14], and that color Doppler ultrasonography may be quite useful for the correct diagnosis of diffuse thyroid infiltration of gastric and other cancers.…”
Section: Introductionsupporting
confidence: 72%
“…Ultimately, together with the PET findings and the cytological examination, we made a diagnosis of metastatic gastric cancer to the thyroid gland. Diffusely metastatic cancer to the thyroid is relatively rare, comprising 6 % of all intrathyroidal metastases [5], and is reported to originate from the lung, bile duct, penis, and stomach cancers [2, 6, 14, 18]. Kim et al summarized ultrasonographic characteristics of 13 cases with diffuse metastasis to the thyroid (9 lung cancers, 2 unknown primary cancers, 1 cholangiocarcinoma, and 1 penile cancer) [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations